Identification of Rare PB2-D701N Mutation from a Patient with Severe Influenza: Contribution of the PB2-D701N Mutation to the Pathogenicity of Human Influenza - Nieto, Amelia; Pozo, Francisco; Vidal-García, Matxalen; Omeñaca, Manuel; Casas, Inmaculada; Falcón, Ana (Frontiers in Microbiology, 2017)
Several amino acid changes have been previously implicated in adaptation of avian influenza viruses to human hosts, among them the D701N change in the PB2 polymerase subunit that also is the main determinant of avian virus pathogenesis in animal models. However, previous studies using recombinant viruses did not provide conclusive information of the contribution of this PB2 residue to pathogenicity in human influenza virus strains. We identified this mutation in an A(H1N1)pdm09-like human influenza virus isolated from an infected patient with pneumonia and acute respiratory failure, admitted to the intensive care unit. An exhaustive search has revealed PB2-D701 as a highly conserved position in all available H1N1 human virus sequences in NCBI database, showing a very low prevalence of PB2-D701N change. Presence of PB2-701N amino acid correlates with severe or fatal outcome in those scarce cases with known disease outcome of the infection. In these patients, the residue PB2-701N may contribute to pathogenicity as it was previously reported in humans infected with avian viruses. This study helps to clarify a debate that has arisen regarding the role of PB2-D701N in human influenza virus pathogenicity.